If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4k + -9 = 7k Reorder the terms: -9 + 4k = 7k Solving -9 + 4k = 7k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-7k' to each side of the equation. -9 + 4k + -7k = 7k + -7k Combine like terms: 4k + -7k = -3k -9 + -3k = 7k + -7k Combine like terms: 7k + -7k = 0 -9 + -3k = 0 Add '9' to each side of the equation. -9 + 9 + -3k = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -3k = 0 + 9 -3k = 0 + 9 Combine like terms: 0 + 9 = 9 -3k = 9 Divide each side by '-3'. k = -3 Simplifying k = -3
| 30*5=x | | a^4+a^3-9a^2-9a= | | h/2x2/h | | 5r-6=1r+3 | | z=4x-4 | | 0=7h^2+10h+3 | | 7/5x | | 5x+47=-1-3x | | 2x+3x+5=50 | | a+54=180-2a | | 4k-9=7k | | 7-2x=2-4 | | (x^-2/4x^-6)^-2 | | 3x-9/40 | | 1-4k-2=-8k | | 7+-8c-48= | | 7(2x-10)-(5-7x)= | | h1/3-4=13 | | 16m^4-25m^2+9= | | 30/4.10 | | 5x+21=6x | | 4x+20=22x-12 | | 50x-5+6x+128+35x+60x=540 | | 56(56-20/4) | | t=(3x+4)(2x-5) | | 2x-3-5= | | x^8+x^4-2= | | 2-5(a-1)=9+a | | 2x-6=5-3 | | a^2x^2+b^2y^2-b^2x^2-a^2y^2= | | (4-w)(3w+2)=0 | | 10.5+6x+7.5=21 |